Strategi Promosi Dinas Pariwisata Pemuda Dan Olahraga Kebupaten Ngawi Dalam Meningkatkan Jumlah Kunjungan Wisatawan Di Taman Wisata Tawun Ngawi - Aliefcelia Tiffany Azzahra; Upik Dyah Eka Noviyanti (Diploma Travel Business, Faculty of Social and Political Science, Jember University, 2022)
Promotion is one of the methods conducted by the tourist attractions managers in increasing tourist visits. Due to that, the Department of Tourism, Youth, and Sports of Ngawi Regency set promotional at Taman Wisata Tawun. This research used a qualitative descriptive method. Data collection techniques were used by conducting interviews, observation, and the documentation. The results of the research can be seen, the promotion strategy of the Department of Tourism, Youth, and Sports of Ngawi Regency in promoting Taman Wisata Tawun by advertising from various media, such as print media, like brochures, booklets, and billboards. Next is social media, namely Instagram, Facebook and YouTube, and electronic media, such as television. Also, through events, such as Keduk Beji, music events, Orek-Orek, Art & Culture Festival, and Pasar Jadul. From the numerous promotional strategies carried out by the Department of Tourism, Youth, and Sports of Ngawi Regency, the promotional obstacles faced by the Department of Tourism, Youth, and Sports of Ngawi Regency in increasing the number of tourist visits at Taman Wisata Tawun is also known.